Alpha-Synuclein species in oral mucosa as potential biomarkers for multiple system atrophy - Zheng, Yuanchu; Cai, Huihui; Zhao, Jiajia; Yu, Zhenwei; Feng, Tao (Frontiers in Aging Neuroscience, 2022)
Background The definitive diagnosis of Multiple system atrophy (MSA) requires the evidence of abnormal deposition of α-Synuclein (α-Syn) through brain pathology which is unable to achieve in vivo. Deposition of α-Syn is not limited to the central nervous system (CNS), but also extended to peripheral tissues. Detection of pathological α-Syn deposition in extracerebral tissues also contributes to the diagnosis of MSA. We recently reported the increased expressions of α-Syn, phosphorylated α-Synuclein at Ser129 (pS129), and α-Syn aggregates in oral mucosal cells of Parkinson’s disease (PD), which serve as potential biomarkers for PD. To date, little is known about the α-Syn expression pattern in oral mucosa of MSA which is also a synucleinopathy. Here, we intend to investigate whether abnormal α-Syn deposition occurs in oral mucosal cells of MSA, and to determine whether α-Syn, pS129, and α-Syn aggregates in oral mucosa are potential biomarkers for MSA. Methods The oral mucosal cells were collected by using cytobrush from 42 MSA patients (23 MSA-P and 19 MSA-C) and 47 age-matched healthy controls (HCs). Immunofluorescence analysis was used to investigate the presence of α-Syn, pS129, and α-Syn aggregates in the oral mucosal cells. Then, the concentrations of α-Syn species in oral mucosa samples were measured using electrochemiluminescence assays. Results Immunofluorescence images indicated elevated α-Syn, pS129, and α-Syn aggregates levels in oral mucosal cells of MSA than HCs. The concentrations of three α-Syn species were significantly higher in oral mucosal cells of MSA than HCs (α-Syn, p < 0.001; pS129, p = 0.042; α-Syn aggregates, p < 0.0001). In MSA patients, the oral mucosa α-Syn levels negatively correlated with disease duration (r = −0.398, p = 0.009). The area under curve (AUC) of receiver operating characteristic (ROC) analysis using an integrative model including age, gender, α-Syn, pS129, and α-Syn aggregates for MSA diagnosis was 0.825, with 73.8% sensitivity and 78.7% specificity. Conclusion The α-Syn levels in oral mucosal cells elevated in patients with MSA, which may be promising biomarkers for MSA.